Evaluasi Penggunaan Surgical Safety Checklist terhadap Kematian Pasien setelah Laparotomi Darurat di Kamar Operasi - Joni Krismanto; Ikhlas Muhammad Jenie (Journal of Telenursing (JOTING), 2021)
This study aims to analyze articles about surgical safety checklists on patient deaths after emergency surgery in the operating room, especially in Indonesia. The literature database search method was carried out on Google Scholar and Pubmed. The literature used is literature that meets the inclusion criteria and was published in the last five years. The results showed that the use of the surgical safety checklist is highly expected to be applied to preoperative and postoperative procedures that reduce surgical complications and determine the evaluation of the use of the surgical safety checklist on patient mortality after emergency laparotomy in the operating room. In conclusion, the application of a surgical safety checklist in emergency laparotomy surgery will be very helpful in reducing the occurrence of errors in operating procedures and complications of emergency laparatomy operations. Keywords: Patient mortality, Emergency Laparotomy, Surgical Safety Checklist